Effects analysis on heat dissipation characteristics of lithium-ion battery thermal management system under the synergism of phase change material and liquid cooling method. (January 2022) - Yi, Feng; E, Jiaqiang; Zhang, Bin; Zuo, Hongyan; Wei, Kexiang; Chen, Jingwei; Zhu, Hong; Zhu, Hao; Deng, Yuanwang
Abstract: In the work, a composite cooling system coupled with PCM (phase change material) and liquid cooling was designed. The influence of parameters such as spacing, EG (expanded graphite) content, battery direction, coolant flow rate and pipe diameter on the cooling performance was analyzed. The results revealed that: (1) The increase of spacing makes the temperature of the pack decrease, but the effect degree of increasing the spacing on temperature performance decreases when the spacing exceeds 14 mm. At the same time, CPCM formed by the added high thermal conductivity material expanded graphite and paraffin can effectively improve the temperature control performance of the pack, which can control the temperature at 313.15K under the condition of an ambient temperature of 308.15K (2) By comparing the maximum temperature and the temperature difference of the pack under different discharge methods, it is concluded that the poles facing inward can reduce the accumulation of the interior heat. (3) The convective heat transfer coefficient and Nu number of the pack are increasing as the flow rate increases, but the slope of the temperature versus flow rate decreasing slowly. After increasing the inlet size, the inner wall surface area of the pipe increases and the average convective heat transfer coefficient of the pack reduces. However, the Nu number increases with the increase of the pipe diameter, indicating that the growth of the pipe diameter can enhance the heat transfer rate. (4) Orthogonal experiment and fuzzy correlation analysis were combined to analyze the parameters that affect the thermal performance of the BTMS. It was determined that using a proper coolant flow rate can maximize the thermal performance of the pack. Highlights: A composite cooling system coupled with PCM and liquid cooling is designed. Influences of the key parameters on the cooling performance are analyzed. Orthogonal experiment and fuzzy correlation analysis are used to analyze affecting parameters. Some results for enhancing cooling performance are obtained.